Total Mikroba Bumbu Inti Instan Skala Industri Rumah Tangga - Yusmila Kumudawati; Yunan Kholifatuddin S (Universitas Muhammadiyah Semarang, 2018)
In today's, for simple cooking, seasosing are now available in instant form. Some seasoning instant made by home industry, produced without preservatives additif. Long deliveries allow spice damage by microbes because although spices have anti-nutritive substances, however seasoning instant still have high moisture content that can cause microbial growth. This study aims to determine the total microbial from main seasoning spice instant produced by home industry atroom temperature storage for 1 day and 21 days. This research is a laboratory experimental research. The number of spice samples there are three types of red, white and yellow are repeated four times and then tested three times (triplo).Samples were investigated on day 1 and 21 storage. Total microbial data analysis by describing data. The results showed that storage seasoning instant for 21 days resulted in an increase of total bacteria in red seasoning from 3.1 x 102 cfu / ml to 4.4 x 103 cfu / ml and white seasoning from 3.9 x 103 cfu / ml to 5.7 x 103 cfu / ml, while the yellow seasoning decrease from 4.8 x 103 cfu / ml to 3.9 x 103 cfu / ml. In the yellow spice, the number of bacteria has decreased and the total amount of bacteria is smallest because in the material there are antimicrobial compounds, notably ginger and turmeric. Although there is an increase in the total number of bacteria in red and white seasoning, but all seasoning during the storage for 21 days still meet the BPOM standard which requires the total amount of bacteria in the seasoning to a maximum of 1 x 104 cfu / ml.Keywords: Total microbial, Shelf time, Main Seasoning Instant, home industry